Hybrid Management for Traumatic Iliac Arteriovenous Fistula - Marinho de Oliveira Góes Junior, Adenauer; Oliveira Feijó, Matheus; Beatriz Araújo de Albuquerque, Fernanda (Journal of Endovascular Resuscitation and Trauma Management, 2023)
Traumatic arteriovenous fistulas are usually the evolution of non-treated contiguous arterial and venous injuries inflicted by firearm projectiles. As time passes, these fistulas can lead to systemic and local repercussions. Endovas-cular management offers great benefit in reducing the risks of open surgery for correcting these fistulas, but unfor-tunately some endovascular resources are not always available.In this situation, a hybrid management offering an endovascular strategy to control bleeding, while allowing an open disconnection of the affected artery and vein, may be useful in dealing with these complex injuries. In this article, the authors report a case of traumatic arteriovenous fistula between the common iliac vessels, managed with a hybrid strategy and make comments about practical issues regarding planning the open part of the procedure and anticipating possible complications when treating such injuries.